Penegakan Hukum terhadap Pertambangan Batu Bara Ilegal di Wilayah Samarinda Kalimantan Timur - Darmin Sumanggi (HUMANIORUM, 2023)
Mining management in Indonesia which is currently given the authority to be delegated to each region that has the potential for natural resources, as stated in CHAPTER VI of the 1945 Constitution of the Republic of Indonesia after the amendment of Regional Government. Article 18 paragraph (5) states that "Regional governments exercise the widest possible autonomy, except for government affairs which are determined by law as affairs of the Central Government". With the results of the study that mining activities without a permit (illegal coal mining) is a criminal act that requires law enforcement efforts against it. The control carried out by Distamben on coal mining without a permit is first through a partnership pattern, secondly, the control with the Satpol PP, and finally the control involves the Samarinda City Police.